Methods for determining pubertal status in research studies: literature review and opinions of experts and adolescents. (17th June 2019) - Walker, I. V.; Smith, C. R.; Davies, J. H.; Inskip, H. M.; Baird, J.
Abstract: In lifecourse studies that encompass the adolescent period, the assessment of pubertal status is important, but can be challenging. We aimed to identify current methods for pubertal assessment and assess their appropriateness for population-based research by combining a review of the literature with the views of experts in the field. We searched bibliographic databases, extracted data and assessed study quality to inform a workshop with 21 experts. Acceptability of different approaches was explored with a panel of ten adolescents. We screened 11, 935 abstracts, assessed 157 articles and summarised results from 38 articles. Combining these with the opinions of experts, self-assessment was found to be a practical method for use in studies where agreement with the gold standard of clinical assessment by physical examination to within one Tanner stage was acceptable. Serial measures of height and foot size accurately indicated timing of the pubertal growth spurt and age at peak height velocity, and were seen as feasible within longitudinal studies. Hormonal and radiological methods did not offer a practical means of assessing pubertal status. Assessment of voice maturation was promising, but needed validation. Young people thought that self-assessment, foot size and voice assessments were acceptable, and preferred an assessor of the same sex for clinical assessment. This review thus informs researchers working in lifecourse and adolescent health, and identifies future directions in order to improve validity of the methods.